Study of the Ternary 1:1:1 Ln(III)-CDTA-Phenyl Alanine/Tyrosine/Tryptophane Complexes - Gaur, Gajendra; Singh, B.P.; Kaurav, M.S. (Asian Journal of Chemistry, 2010)
1:1:1 Ln(III)-CDTA-L mixed ligand complexes have been investigated by potentiometric titration method [Ln(III) = Tb(III), Dy(III), Ho(III) and Er(III), CDTA = cyclohexane diamine N,N,N`,N`-tetraacetic acid and L = phenyl alanine/tyrosine/tryptophane]. The stability constants of these ligands together with free energy of formation and entropy change at different ionic strengths (μ = 0.05, 0.10 and 0.15 M KNO3) and varying temperatures i.e. 25, 35 and 45 ºC have been investigated in aqueous medium. Thermodynamic parameters e.g., ΔG, ΔH and ΔS have been calculated. Relative order of stabilities of the complexes observed as Tb(III) < Dy(III) < Ho(III) < Er(III) and with respect to ligand it was phenyl alanine < tyrosine < tryptophane.